(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
There has been increasing informalization of activities through well-established linkages between formal and informal activities and organized and unorganized sector. For faster growth and inclusiveness there has to be emphasis on the informal sector and its development specially women through addressing needs of skill, technology, dignity of workforce, social security, infrastructure and marketing. A clear policy is imperative for non-agricultural jobs engaging female workers with emphasis on quality of jobs. This paper describes the profile like nature of work, industry of work, working conditions, hours of work, work related benefits. Secondly, it also estimates the persistence of Informality in female workers of the informal sector. The study has adopted a descriptive method of research and investigational approach with sample size of 359 respondents. The paper brings forward that in the informal sector of Delhi, self-employment among female workers belonging to adolescence and as adult women workers remains the main choice of the work As far as working hours are concerned the younger females work longer durations as compared to women more than 19 years as they are engaged in taking care of children, sick adults, domestic chores, etc. Despite working at home, they seek gainful engagement in the informal sectors as per the time they could devote to contributing to the family economically. Poverty, inadequate family income, meeting demands of bad habits of male members, tradition for women to work is the major persisting reasons for their working in the informal sector.